Social economic perspective after pandemic era in Malaysia in 2024 / Mohd Azlan Abdul Majid and Afizan Amer - Abdul Majid, Mohd Azlan; Amer, Afizan (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2024)
The COVID-19 pandemic struck The Word from 2019 until a few years ago. Malaysia also had a negative social and economic impact because the Malaysian government was not excluded from initiating a similar program to mitigate the infection of the virus by quarantine and restrictions on human mobility and movement. Movement Control Order or MCO is starting in Malaysia on 18 March 2020. This creates two fundamental consequences. Health and economics. Of course, health is a significant objective of this order, but this also influences economic growth and, importantly, social. We can see the recent data from the World Bank to determine this correlation. Malaysia's GDP by current USD in 2019 was at 365.18 billion USD. However, in 2020, GDP fell to 337.46 billion USD. However, in 2021, Malaysian GDP had a V-shape recovery pattern of 373.83 billion USD. Impressive right? Not necessary. This is because in 2018 Malaysian Gini Index was at 0.407 in 2009, 0.411 in 2020 and 0.407 in 2021, based on the World Bank and the Department of Statistics in Malaysia. This means that there exists economic growth. However, income inequality exists in COVID-19, but there is a quick recovery after 2021. If this argument holds?